What do Australian health consumers believe about commercial advertisements and testimonials? a survey on health service advertising - ACL Holden; S. Nanayakkara; J. Skinner; H. Spallek; W. Sohn (BMC, 2021)
Abstract Background There has been little examination of consumer attitudes towards the commercial advertising of healthcare services in Australia and how marketing is used by consumers in their health decision-making. In this research, we examined how consumers reported commercial advertising helped them to understand the health services available to them and the influence that marketing had upon their choices. Methods A survey instrument using a Likert scale to indicate agreement or disagreement with 21 questions was developed using qualitative interviews before being distributed online within Australia. Sampling of participants was stratified by age, gender and location. The results were subjected to statistical analysis with Spearman Rank Correlation test being used for bivariate analysis. Results One thousand five hundred sixty-four complete surveys were collected. The results revealed certain consumer beliefs, for example; the title of 'Dr' was believed to indicate skill and high levels of training (81.0%), with 80.3% agreeing incorrectly that use of the title was strictly regulated. Participants reported to have a higher confidence in their own abilities (71.2%) than the public (52.8%) in assessing health advertising. The level of self-confidence increased with higher education level and decreased by age (p < 0.05). Testimonials were reported to be lacking in reliability (67.7%) and that they should not be used in healthcare in the same manner as they are used in other industries. Only 44.8% of participants reported that they felt confident to spot a review that was not written by a genuine user of a service. Conclusions The data demonstrated that many health consumers felt that while commercial health advertising was helpful, it was also confusing, with many participants also holding mistaken beliefs around other elements of commercial health advertising. While the advertising of healthcare services might have educational effects and be superficially empowering, advertising is primarily intended to sell, not educate. This research demonstrates that there is significant potential for healthcare advertising to mislead. Future developments in regulatory health advertising policy, and the related ethical frameworks developed by professional healthcare associations, need to consider how the consumers of healthcare services might be better protected from misleading and predatory advertising practices.